Evaluation of antiangiogenic potential of lubiprostone, a clc-2 channel agonist by chorioallantoic Membrane assay. (cam) - CHANDANA KAMILI,; K. RAVI SHANKAR,; UMA MAHESHWARARAO VATTIKUTTI,; R. AAMUKTA, (International Journal of Pharma and Bio Sciences, 2016)
Angiogenesis is the formation of new blood vessels. Abundant ion channels are located on the endothelial cell surface. Ion channels have significant role in cell proliferation and thus in vascular angiogenesis. The antiangiogenic activity of a specific voltage gated Chloride channel opener ClC2 (Lubiprostone) was evaluated by Chorioallantoic Membrane (CAM) Assay (in ovo).The standard antiangiogenic drug used for comparison was Bevacizumab. All the data obtained from the experimental groups have been compared to the control group. The data was analyzed by one-way ANOVA followed by post hoc test, the Dunnett’s test to compare mean of every group with the control mean, using graph pad prism5.0 software. In the CAM assay, the parameters evaluated were number of branches per unit area and angiogenic score. Medium (Lubiprostone 10-5M /egg) and high (Lubiprostone 10-4M /egg) doses of both the channel blockers gave significant results. From the results obtained, Lubiprostone has effective anti-angiogenesis which may be therapeutically beneficial .The molecular pathways may be due to negative regulation of cell volume, cell migration and thus proliferation.